KEANEKARAGAMAN SPESIES BURUNG DI HUTAN MANGROVE PILOHULATA GORONTALO UTARA - Ernikawati, Ernikawati; Puspaningrum, Dian; Yusuf, Moh. Aristya (MAKILA, 2024)
Birds play an essential role in the mangrove ecosystem because they can help improve forests by natural means such as pollinating flowers and spreading seeds. The diversity of bird species found in an area can indicate the conditions in that area. Mangrove forests are essential in an area because they are a habitat for wildlife, especially birds. This research aims to determine the diversity of bird species in the Pilohulata Mangrove Forest. The method used in this research was the Concentration Counts method. The study showed that the diversity of bird species was found in as many as 16 bird species from 15 families with 177 individuals and 11 orders. The diversity index value is 3.030 with high index criteria, the evenness index is 0.60 with evenly distributed criteria, and the bird richness index is 2.90 with medium richness index criteria.